Momentary associations between stress and physical activity among children using ecological momentary assessment. (July 2021) - Do, Bridgette; Mason, Tyler B.; Yi, Li; Yang, Chih-Hsiang; Dunton, Genevieve F.
Abstract: Chronic and acute stress may have a detrimental effect on children's physical activity. Research on stress as a predictor of children's physical activity has mostly focused on stress between children, rather than how children's within-day variation in stress may predict physical activity. The current study assessed the within- and between-effects of stress on subsequent physical activity in three different time windows using ecological momentary assessment (EMA) and accelerometry. Children (N = 190; MBaseline Age = 10.1 ± 0.9, 53% female, 56% self-identified Hispanic/Latino) completed six semi-annual assessment bursts across three years. During each burst, participants responded to up to seven (weekend) or three (weekday) randomly prompted EMA surveys on smartphones for seven days and wore a waist-worn accelerometer. Multi-level structural equation modeling examined within- and between-subjects effects of stress as a predictor of children's subsequent moderate-to-vigorous physical activity (MVPA) in the 15, 30, and 60 min following the EMA prompt. Latent variables were created for within- and between-subjects stress were comprised of three EMA stress items. Higher than average levels of stress (within-subjects) significantly predicted lower MVPA in the subsequent 15, 30 and 60 min ( p s < .05). Between-subjects stress was not significantly associated with subsequent MVPA ( p s > .05). Results indicate that elevated momentary stress predicts less subsequent MVPA. These findings suggest that within-day fluctuations in stress may be a barrier for children engaging in physical activity. Childhood physical activity promotion and interventions should consider the role of children's stress, aim to reduce the stress children experience throughout the day, and incorporate stress coping strategies. Highlights: Momentary variations in stress predicted children's subsequent physical activity. When children reported more stress than usual, they did less physical activity. Between-subjects stress was not associated with physical activity. Momentary stress may have an immediate and acute impact on physical activity.